Assessing the carbon sink capacity of coastal mariculture shellfish resources in China from 1981–2020 - Gu, Yixin; Lyu, Shaoliang; Wang, Lifei; Chen, Zhijie; Wang, Xuefeng (Frontiers in Marine Science, 2022)
The ocean has considerable potential to function as a carbon sink, absorbing anthropogenic CO2 and buffering the effects of climate change. How the culture of shellfish can be used to increase the ocean carbon sink warrants evaluation. We analyze the production and carbon sink capacity of six important mariculture shellfish species (oyster, ark clam, mussel, scallop, clam, and razor clam) in nine coastal provinces of China from 1981–2020 using quality assessment and logarithmic mean Divisia index (LMDI) decomposition methods. Over this time period both cultured shellfish production and its contribution to the carbon sink generally increase, averaging approximately 600,000 t annually over the last four decades. Both the annual production and carbon sink capacity of China’s mariculture shellfish industry vary geographically. The total annual tonnage (scale) of cultured shellfish, and to a lesser extent, coastal shellfish species composition (structure) influence carbon sink capacity, and affect China’s plans to achieve “dual carbon goals.” Combining historical analysis and the LMDI method, we propose a scheme that optimally and more sustainably manages China’s culture of shellfish.